Working memory capacity as a predictor of text idea recall in multitasking L2 digital reading - de Azevedo, Bruno; Oliveira, Davi Alves; Finger, Ingrid; Tomitch, Leda Maria Braga (Psicologia, reflexão e crítica, 2025)
Background Digital reading in a second language is a cognitively demanding task constrained, among other factors, by individuals’ working memory resources. Additionally, listening to music whilst reading might overload working memory. However, previous studies found mixed results regarding the effects of music in reading comprehension. Objective This study investigates the effects of working memory capacity on English as a second language digital reading comprehension in a multitasking setting. More specifically, it examines how working memory capacity influences the ability to recall text ideas (main ideas, secondary ideas, and details) after reading a digital text in a second language and simultaneously listening to music. Method The between-subject design study was conducted with sixty-five participants aged 19–62 years ( M = 28.87; SD = 8.20) divided into two groups of Brazilian Portuguese-English proficient bilinguals, one reading while listening to lyrical music and the other reading while listening to non-lyrical music. Participants’ working memory capacity was assessed using a Self-Applicable version of the Reading Span Test, and their reading comprehension of a second language digital text was assessed with a free-written recall. Participants also rated their proficiency in their L2. Results Findings suggest that individuals with higher working memory capacity are better at recalling secondary ideas and details, while no effect was observed in the recall of main ideas. Additionally, no difference between groups (lyrical vs non-lyrical) was observed. An exploratory complementary analysis indicates that readers who recall secondary ideas tend to better recall main ideas, so higher working memory capacity seems to enable the recall of secondary ideas in addition to main ideas. Conclusion This study contributes to understanding cognitive resource allocation in second language digital reading and the potential effects of multitasking on reading comprehension.